EFICIÊNCIA DE UTILIZAÇÃO DE NUTRIENTES EM CULTIVARES DE FEIJÃO EM RAZÃO DA CALAGEM - Silva, Laerte Marques da; Lemos, Leandro Borges; Crusciol, Carlos Alexandre Costa; Mateus, Gustavo Pavan; Feltran, José Carlos (REVISTA DE AGRICULTURA, 2015)
EFICIÊNCIA DE UTILIZAÇÃO DE NUTRIENTES EM CULTIVARES DE FEIJÃO EM RAZÃO DA CALAGEM